South-western federal taxation 2021 : corporations, partnerships, estates & trusts / William H Hoffman ...[et al] - Hoffman, William H.
Gain a thorough understanding of today's corporate tax concepts and most current tax law with SOUTH-WESTERN FEDERAL TAXATION 2021: CORPORATIONS, PARTNERSHIPS, ESTATES & TRUSTS, 44E and accompanying professional tax software. This reader-friendly presentation emphasizes the latest tax law and changes impacting corporations, partnerships, estates and trusts. You examine the most current tax law at the time of publication. Complete coverage of the Tax Cuts and Jobs Act of 2017 offers guidance from the Treasury Department. Clear examples, summaries and tax scenarios further clarify concepts and help you sharpen critical-thinking, writing and research skills. Each new book includes access to Intuit ProConnect tax software, Checkpoint (Student Edition) from Thomson Reuters, CNOWv2 online homework solution and MindTap Reader. Learn how taxes impact the corporate world today as you prepare for the C.P.A. exam or Enrolled Agent exam or begin study for a career in tax accounting, financial reporting or auditing.